ANALISIS POSTUR KERJA SHELVING PADA PERPUSTAKAAN FAKULTAS ILMU BUDAYA UNIVERSITAS GADJAH MADA - Perdani, Azzahra Putri; Rahmayani, Amalia Azka (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Shelving is a crucial task in library operations, where librarians arrange library materials on shelves systematically based on classification numbers. To optimize space usage, bookshelves are typically designed with multiple levels. This design requires librarians to reach overhead or squat down when accessing items on the topmost or bottommost shelves. Repetitive shelving activities performed over extended periods can lead to fatigue and an increased risk of musculoskeletal injuries, especially in the upper body. This study aims to assess the working posture of library staff at the Faculty of Cultural Sciences, Universitas Gadjah Mada, during shelving activities using the Rapid Upper Limb Assessment (RULA) method. The study adopts a qualitative observational approach, with the RULA worksheet serving as the main assessment tool. Findings reveal that five out of six library staff members obtained a RULA score of 7, indicating a very high ergonomic risk. One staff member achieved a lower score due to the use of an assistive device—a small chair—while working. Based on these results, it is recommended that improvements be made to working posture and that ergonomic aids be provided to reduce injury risks and enhance employee comfort during shelving tasks.